The Rise of Radicalism and Terrorism in Indonesia and Malaysia - M. Zaki Mubarok; Ahmad Fauzi Abdul Hamid (Review of Islam in Southeast Asia, 2018)
This article examines the dynamics of radicalism and terrorism in Indonesia and Malaysia and how government from both countries responded to the rise of radicalism and terrorism. It discusses the development of terrorism in Southeast Asia from the period of Darul Islam in 1950s to Jama’ah Islamiyah in 2000s. In addition, it argues that Indonesia and Malaysia have become barometer of terrorism networks in Southeast Asia. Radicalism and terrorism networks also have transformed the character of Islam in Southeast Asia, and this certainly challenges the future of mainstream Muslims in the region who are recognized as maintaining moderate and peaceful Islam. This is based on interviews to terrorist and former terrorist detainees and government officials in Indonesia and Malaysia. It also comes from analysis of books and documents from radical-jihadist organizations and government. It recommends state and civil society policy to unite in preventing and countering radicalism and terrorism in Southeast Asia, especially in Indonesia and Malaysia.